Selective class II HDAC inhibitors impair myogenesis by modulating the stability and activity of HDAC‐MEF2 complexes. (26th November 2020) - Nebbioso, Angela; Manzo, Fabio; Miceli, Marco; Conte, Mariarosaria; Manente, Lucrezia; Baldi, Alfonso; De Luca, Antonio; Rotili, Dante; Valente, Sergio; Mai, Antonello; Usiello, Alessandro; Gronemeyer, Hinrich; et al.
Abstract :